Manajemen Strategis Sekolah dalam Mengelola Ketergantungan AI dan Dampaknya pada Berpikir Kritis: Studi Kasus di SMA Maarif 1 Pamekasan - Fina Tamara El-Haris; Zeinal Abidin; Imdadur Rohman (re-JIEM (Research Journal of Islamic Education Management), 2026)
The rapid development of Artificial Intelligence (AI) over the past decade has significantly transformed the educational landscape, including the increasing use of AI platforms by students to complete academic tasks. This phenomenon raises concerns regarding the potential decline in students’ critical thinking skills due to excessive reliance on technology. This study aims to analyze school management strategies in addressing AI dependency and its impact on students’ critical thinking skills at SMA Ma’arif 1 Pamekasan. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and document analysis. The findings indicate that AI usage among students is widespread, particularly for writing essays, summarizing materials, and preparing presentations. However, the school has not established formal policies regulating AI usage, resulting in fragmented and uncoordinated responses from teachers. High dependency on AI tends to correlate with a decline in students’ argumentation quality and analytical abilities. Nevertheless, AI also holds potential as an effective learning tool when used strategically and supported by adequate digital literacy. The SWOT analysis reveals strengths in the school’s foundational values and teachers’ adaptability, while weaknesses include the absence of formal policies, limited training, and insufficient evaluation systems. This study recommends developing clear AI usage policies, enhancing digital literacy for teachers and students, designing higher-order thinking-based learning, and implementing data-driven monitoring systems to ensure the productive use of AI while maintaining students’ critical thinking skills.